Studi analisis kesulitan siswa kelas VIII SMP madani dalam mengerjakan soal statistika ditinjau berdasarkan gender - Ambar Rahayu Nurmatin; Eka Senjayawati (IKIP Siliwangi, 2023)
This research looks at how difficult it is for grade VIII students of junior high school in working on statistical problems in terms of gender. Qualitative descriptive method was used for this research. 8 students consisting of 4 male students and 4 female students from Madani Middle School in Cihampelas were used as research subjects. The instrument used in this research has four items in the form of descriptions. The results of student test scores based on statistical question instruments are used in collecting research data, with indicators; 1) evaluating the accuracy of the data provided, 2) determining the mean value of a data, 3) analyzing data in the form of diagrams, 4) solving problems to draw a conclusion. Based on the analysis and discussion of the 4 questions describing the statistics material, it can be concluded that the ability of class VIII male students at Madani Middle School in working on statistical problems is still weak compared to female students. The students' lack of understanding of the basic concepts of statistics, the inability to understand the meaning of the questions, and the difficulty in finding strategies to solve problems are the contributing factors.